THE AUTOMATED CONTROL SYSTEM OF PARAMETERS OF STATIONARYAND MOBILE OBJECTS - Valery Petrovich Mochalov; Natalia Yurievna Bratchenko; Sergey Vladimirovich Yakovlev (Современная наука и инновации)
Nowa days the need of automated evaluation of technical conditions of existing power plants, pipelines, various engineering structures requires the implementation of methods of nondestructive control and technical diagnostics. Most of the decisions in this area based on wireless data transmission technologies that can significantly reduce deployment time and system modernization, and increase its survivability compared to the wired version of the implementation